1989
DOI: 10.1099/00221287-135-3-525
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between the Production of Spirosomes and Anaerobic Glycolysis Activity in Escherichia coli B

Abstract: The effects of culture conditions (aerobic or anaerobic) and glucose in the medium on the production of spirosomes in Escherichia coli B were studied by SDS-PAGE and electron microscopy. The M, of the spirosome of E. coli B was estimated to be 97000. Electron microscopy revealed that the amount of spirosomes derived from anaerobic cultures was about eightfold larger than that from aerobic cultures. In SDS-PAGE, the bands of spirosome protein derived from anaerobic cultures were more intense than those derived … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
16
0

Year Published

1990
1990
2008
2008

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 4 publications
(4 reference statements)
1
16
0
Order By: Relevance
“…Purification of proteins for in vitro tests. After prolonged incubation of E. coli under oxygen depletion, AdhE forms large active oligomers which can be isolated from bacterial cell extracts by ultracentrifugation (Matayoshi et al, 1989;Kessler et al, 1992); therefore, we applied a one-step AdhE purification method. After testing different growth conditions, we found that almost homogeneous enzyme could be isolated from E. coli cells growing microaerobically at 25 uC, in M9 minimal medium with 0.2 % glucose.…”
Section: Introductionmentioning
confidence: 99%
“…Purification of proteins for in vitro tests. After prolonged incubation of E. coli under oxygen depletion, AdhE forms large active oligomers which can be isolated from bacterial cell extracts by ultracentrifugation (Matayoshi et al, 1989;Kessler et al, 1992); therefore, we applied a one-step AdhE purification method. After testing different growth conditions, we found that almost homogeneous enzyme could be isolated from E. coli cells growing microaerobically at 25 uC, in M9 minimal medium with 0.2 % glucose.…”
Section: Introductionmentioning
confidence: 99%
“…Residues 1-449 and 763-890 of AdhE are involved in its polymerization and may also be responsible for the propensity of the protein to aggregate amorphously. The biological significance of spirosomes, however, remains enigmatic (3,5,6).Despite the reversibility of the two NADH-coupled reactions catalyzed by AdhE, wild-type E. coli is unable to grow on ethanol as a sole source of carbon and energy, because the adhE gene is transcribed aerobically at lowered levels (7-9) and the half-life of AdhE activity is shortened during aerobic metabolism by metal-catalyzed oxidation (MCO). During this process, the hydroxyl radicals locally generated by the Fe 2ϩ bound to AdhE covalently attack the amino acid side chains near the active site (10, 11).…”
mentioning
confidence: 99%
“…Residues 1-449 and 763-890 of AdhE are involved in its polymerization and may also be responsible for the propensity of the protein to aggregate amorphously. The biological significance of spirosomes, however, remains enigmatic (3,5,6).…”
mentioning
confidence: 99%
“…There have been many reports on morphological, biochemical and immunochemical studies of spirosome as quoted in our previous papers (Yamato et al, 1994(Yamato et al, , 1995. Though some functional aspects of spirosome have been described so far Matayoshi et al, 1989), its function is not yet well understood.…”
mentioning
confidence: 99%